Chemical constituents isolated from stems of Maesa membranacea - Nguyen Thanh Le; Huu Giap Tran; Thi Kim Oanh Vu; Thuy Duong Pham; Ngoc Thuc Dinh; Anna Stojakowska; Bich Ngan Truong (Vietnam Journal of Science, Technology and Engineering, 2020)
Maesa membranacea A. DC. (Myrsinaceae) has been traditionally used for the treatment of fever and hepatitis. The phytochemical investigation of Maesa membranacea stems has led to the isolation of six compounds including kaempferol (1), (-)-epicatechin (2), betulinic acid (3), p-hydroxybenzoic acid (4), vanilic acid (5), and protocatechuic acid (6). The chemical structures of these compounds have been determined by nuclear magnetic resonance (NMR), mass spectrometry (MS) data, and by comparison with previously reported works. This is the first report of a chemical study on Maesa membranacea as compounds 1-6 listed above were found from the Maesa genus for the first time.